Green Politics and the Policy Cycle in Indonesia's Electrification Journey: A Comparative Analysis of Policy Priorities for Electric Cars and Public Transport - Perdana, Adani; Tjioediningrat, Rudolph; Rizkiawan, Slamet (Journal of Batteries for Renewable Energy and Electric Vehicles, 2024)
This paper presents a comprehensive Descriptive Study and Document Analysis of policy priorities for electric cars and public transport in Indonesia, within the context of the country's electrification journey. Utilizing secondary data sources including policy documents, government reports, academic studies, and news articles, we apply the principles of Green Politics and the stages of the Policy Cycle to interpret our findings. Our comparative analysis reveals distinct policy priorities for electric cars versus public transport, with implications for Indonesia's environmental, economic, and social goals. We discuss these findings in relation to the principles of Green Politics and the stages of the Policy Cycle, providing insights into the political and policy dynamics shaping Indonesia's electrification journey. The paper concludes with recommendations for future policy priorities and strategies, aimed at promoting a more sustainable and equitable transition to electric mobility in Indonesia, and suggests areas for future research. Our research contributes to the growing body of literature on electrification policies in developing countries, and offers valuable insights for policy makers, industry stakeholders, and researchers